If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = -6x + -6 + 7x Reorder the terms: 4 = -6 + -6x + 7x Combine like terms: -6x + 7x = 1x 4 = -6 + 1x Solving 4 = -6 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + -1x = -6 + 1x + -1x Combine like terms: 1x + -1x = 0 4 + -1x = -6 + 0 4 + -1x = -6 Add '-4' to each side of the equation. 4 + -4 + -1x = -6 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = -6 + -4 -1x = -6 + -4 Combine like terms: -6 + -4 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| (12x^4b^11)/(10ab^3)=0 | | 1700*1.333*12=x | | (2-7)(z+5)=0 | | 8(-12-2)= | | 6-2x+11=13 | | 22+2x=-50 | | 0.04(2c-30)=-0.08(c-4) | | f(x+h)=x^2+5x+9 | | -1.5y=3+2.4x | | (8-u)(2u+9)=0 | | 99/198 | | 20+5=-5(3x-5) | | x^2/4-x/4=2 | | 80x+20=x | | ln(x/71)=-2.34290 | | 4x+12=7x+15 | | .5n-6=1 | | -3y=6+1.5x | | 27=108 | | 13y-6=3y-6-6 | | 3.4+10m=7.93 | | 15287ft=2.9mi | | x-6*2x=24 | | -2y+4=-14+8y | | -7x-32=x+13 | | -3(3y-7)-y=-3(y-5) | | 8.48x-2.6=-7.17x-7.1 | | h=55-20t-5t^2 | | -2y-7=15 | | 3/4(x-4)=2(x-1) | | -10v-10=9v-8 | | .25(n+2)=1 |